Lighting for digital video and television - Jackman, John, 1957- (Routledge, Taylor & Francis Group, 2020)
"This book gives a comprehensive overview of lighting equipment and techniques for digital production. Suitable for either beginners or more advanced users, the fully updated fourth edition covers human sight vs. film or video, the basic issues of contrast and exposure, with explanation of how exposure of digital video differs from analog video or film, electrical connectors, requirements, electrical load management, safety issues, and the latest LED systems. A variety of basic lighting setups for different situations are explained, with clear diagrams and photos showing the "look" of each approach. Techniques for shooting in available light and dealing with color problems in mixed lighting situations is examined. More advanced film-style lighting is covered, especially techniques in creating a convincing realistic look. A special section deals with solutions to common problems, ranging from reflections on glasses and dealing with white walls to lighting very light-skinned and very dark-skinned subjects in the same shot. Special lighting situations, such as lighting night scenes or bluescreen sets, are covered in detail, with studio lighting covered in a dedicated separate chapter. The book is also peppered with anecdotes and trivia about lighting techniques and the lighting trade. It is the ideal text for both beginners studying lighting and cinematography, as well as more advanced practitioners"--
Terminologický slovník
Keywords: filmování; videozáznamy; digitální videozáznam; televize; osvětlení; světelná technika; cinematographic filming; video recording; digital video recording; television; lighting; lighting technology; příručky; handbooks, manuals, etc